If it's not what You are looking for type in the equation solver your own equation and let us solve it.
4(3x+8)=19x+3-7x+29
We move all terms to the left:
4(3x+8)-(19x+3-7x+29)=0
We add all the numbers together, and all the variables
4(3x+8)-(12x+32)=0
We multiply parentheses
12x-(12x+32)+32=0
We get rid of parentheses
12x-12x-32+32=0
We add all the numbers together, and all the variables
=0
x=0/1
x=0
| 8h+10=70 | | 4(y−7)=2y−38 | | 81x-27=9(9x-3) | | 5x+27x-8=8(4x+6) | | x+41=8(x+7) | | 17x+2+7x-10=(4x+15) | | 5(2x-10)÷2+14=9 | | 64^-3x-3•64+22=38 | | 41x+57=41x+42 | | 6u-u=35 | | 12x+5=1x+49 | | 5(2x-10)/2+14=9 | | 7x+5x-2=3(4x+7) | | 8=3w-w | | 12(x+5)=13x+5 | | 15x-38+8x-1=(3x+2) | | 20x-3=5(4x+1) | | 15=-2k+3 | | 17+8y=6 | | 4/5^2=1/10x | | P2-p-42=O | | -12-14=142y | | 5(19-x)=-65 | | 12x=5+x+49 | | 4a-6=142 | | 14=5u+4 | | x-19(-5)=-65 | | 6m+18=80 | | 4x+51=8x-13 | | -5=-7+2y | | 7x-6=8(11-3) | | 8-x/3=-16 |